2021
DOI: 10.3390/ijms22137004
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic 5′-Nucleotidase II Silencing in Lung Tumor Cells Regulates Metabolism through Activation of the p53/AMPK Signaling Pathway

Abstract: Cytosolic 5′-nucleotidase II (cN-II) is an allosteric catabolic enzyme that hydrolyzes IMP, GMP, and AMP. The enzyme can assume at least two different structures, being the more active conformation stabilized by ATP and the less active by inorganic phosphate. Therefore, the variation in ATP concentration can control both structure and activity of cN-II. In this paper, using a capillary electrophoresis technique, we demonstrated that a partial silencing of cN-II in a pulmonary carcinoma cell line (NCI-H292) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[ 5 ] In recent years, cancer susceptibility and development are associated with NT5DC family members. The expression of NT5C2 plays an important role in lung cancer, [ 10 ] acute leukemia, [ 35 ] and astrocytoma. [ 36 ] In breast cancer, by regulating ROS metabolism and defense, NT5C2 regulates cellular responses to glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] In recent years, cancer susceptibility and development are associated with NT5DC family members. The expression of NT5C2 plays an important role in lung cancer, [ 10 ] acute leukemia, [ 35 ] and astrocytoma. [ 36 ] In breast cancer, by regulating ROS metabolism and defense, NT5C2 regulates cellular responses to glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In lung tumor cells, the silence of NT5C2 opposes the cancer phenotype, activates the p53/AMPK pathway and regulates metabolism. [10,11] Raza et al [12] showed that NT5C2 deficiency facilitates tumor growth, response to chemotherapeutic and migration. When treating non-small cell lung cancer cells with gemcitabine and platinum, the expression of NT5C2 can be used as an indicator of response.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that lung cancer patients with high NT5C2 expression had poor prognosis, and the reduction of NT5C2 could increase the sensitivity to gemcitabine [ 21 ]. Another study displayed that silencing NT5C2 increased oxidative metabolism and reduced lung cancer cell proliferation by activating p53 and AMPK [ 22 ]. In glioblastoma, NT5C2 could regulate tumor cell proliferation and drug sensitivity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors report that the manipulation of cN-I is more efficient in regulating AMP intracellular concentrations and AMPK activity [ 176 ]. Recently, cN-II silencing in tumor cells of epithelial origin indicated that a total absence of cN-II expression was followed by a decrease in proliferation and motility, and the activation of AMPK and p53 [ 177 ]. So far, it has been reported that cN-II was silenced in zebrafish [ 178 ], in Drosophila [ 179 ], and in mouse [ 180 ].…”
Section: 5′-nucleotidasesmentioning
confidence: 99%